Math, asked by Tanushreddy05, 1 month ago

Could anyone briefly explain (A^3 plus B ^3 plus C^3)

Answers

Answered by sshubhi129
1

Answer:

a3+b3 + c3 = (a+ b + c) (a2 + b2 + c2 – ab – be – ca) + 3abc

[using identity, a3+b3 + c3 – 3 abc = (a + b + c)(a2+b2+c2 –ab–bc-ca)] = 0 + 3abc [∴ a + b + c = 0]

a3+b3 + c3 = 3abc. 

Step-by-step explanation:

if you like the answer please follow or mark me as a brainlist .

Answered by Anonymous
2

Answer:

Refer to the above attachment !

Attachments:
Similar questions